An organizational perspective on applied sport psychology in elite sport. (May 2019) - Wylleman, Paul
Abstract: While research on applied sport psychology (ASP) has generally focused on the development and professional practice of its practitioners, less attention has been paid to the role of organizations. The aim of this article consisted of reflecting on the role of organizations on the development of ASP practitioners and the quality of their services. Using FEPSAC's position statement on the quality of applied sport psychology services, the role of two types of organizations - a sport psychology and an elite sport organization - on the development of ASP practitioners and the quality of their services was reviewed. After providing an overview of initiatives related to ASP as developed or supported by FEPSAC, the role of elite sport organizations ensuring high-quality ASP services was described. Throughout the article, reflections and recommendations are provided on how the development of ASP practitioners and the provision of ASP services can be supported and enhanced. The article concludes with suggestions on the role both types of organizations can play in the quality management of ASP services. Highlights: FEPSAC took and supported five applied sport psychology related initiatives during the past decade. The quality of elite sport organizations' applied sport psychology (ASP) services can be analyzed using a framework of quality management. Sport psychology and elite sport organizations can both further the development of ASP practitioners and provision of ASP services.